A REVIEW METHOD FOR IDENTIFICATION OF RARE AND ENDANGERED PLANTS THROUGH DNA BARCODING (International Association of Biologicals and Computational Digest, 2022)
DNA barcoding is a new concept. It has been developed for providing fast, precise and automatable species identification which uses standardized DNA sequences as tags. DNA barcoding can provide the taxonomists; conservationists. The early goal of the DNA barcoding process is to build online libraries of barcode sequences for all known species that can serve as a standard to which DNA barcodes of any identified or unidentified specimens can be matched. This can improve several inherent problems related with traditional taxonomic identification, based on morphological characters, such as incorrect identification of species due to phenotypic plasticity and genotypic variability of the characters, such as incorrect identification of species due to phenotypic plasticity and genotypic variability of the characters, overlooking cryptic taxa, difficulty in finding reliable characters due to long maturity periods (CBOL Plant Working Group, 2009). It is particularly of much use in areas where species identification with morphological characters is not practicable due to widespread damage or delayed expression. It should be enduring in mind that DNA barcoding is not an alternative to taxonomy, and it cannot replace taxonomy as such, but is a useful tool that creates information on unknown taxa. In this paper, methods of the process of selecting and redefining barcodes for plants evaluation of the factors which manipulate the discriminatory power of the advance with some early applications of DNA barcoding are discussed and then added the authors’ for their views and recommendations.
Keywords: DNA Barcode,rbcL, matK, Agarose Gel Electrophoresis, Sanger sequencing, Rare, Endangered Plants